Teacher training needs and youth and adult education: challenges and learnings (Research, Society and Development, 2020)
This study sought to analyze and discuss the main teacher training needs with regard to Youth and Adult Education (EJA). The research aimed to answer the following research question: Is it possible to present something fruitful that helps the thinking and acting of the teachers involved with the EJA classroom? Thus, the objective of the study was to analyze and discuss the “training needs” category as a fundamental strategy in the training of Youth and Adult Education (EJA) teachers and its importance for building the general principles that can support the necessary training for teachers involved and thus better respond to their reality. As for the methodology, we used exploratory research, of a descriptive nature and applied a semi-structured interview for data collection. As a result, we point out the teachers' problems and difficulties, that is, the fundamental training needs that they would like to know, review, and deepen, in the perspective of improving their pedagogical practice in EJA. We conclude that the “training needs” category is a fundamental and strategic element in the organization of continuing education, requiring time, research and further research on the topic.